PENGARUH PROFESIONALISME, INDEPENDENSI, KOMPETENSI DAN TANGGUNGJAWAB AUDITOR TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (SURVEY PADA AUDITOR DI KAP WILAYAH SUMATERA) - Hutabarat, Julia Fitri; -, Kamaliah; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This reserch aims to examine the effect of professionalism, independent, competent and auditor responsibility which consist of ability for detect fraud in public accounting in sumatera in 2014.This study uses primary data. Sample selection technique used is purposive sampling. Fifty six of auditor that meet the sample criteria has been selected. The analytical method is multiple linear regression using SPSS version 20. The result shows that professionalism, independent, competent and auditor responsibility have a significant influence on auditor ability for detect fraud.   Keywords: Profesionalism, Independent, Competent, Auditor responsibility and Auditor ability for Detct Fraud.